Reactive oxygen species and nitric oxide mediate plasticity of neuronal calcium signaling - Yermolaieva, Olena (The National Academy of Sciences, 2000)
Reactive oxygen species (ROS) and nitric oxide (NO) are important participants in signal transduction that could provide the cellular basis for activity-dependent regulation of neuronal excitability. In young rat cortical brain slices and undifferentiated PC12 cells, paired application of depolarization/agonist stimulation and oxidation induces long-lasting potentiation of subsequent Ca(2+) signaling that is reversed by hypoxia. This potentiation critically depends on NO production and involves cellular ROS utilization. The ability to develop the Ca(2+) signal potentiation is regulated by the developmental stage of nerve tissue, decreasing markedly in adult rat cortical neurons and differentiated PC12 cells.